FPGA-based optimal robust minimal-order controller structure of a DC–DC converter with Pareto front solution. (October 2016) - Sadek, Uroš; Sarjaš, Andrej; Chowdhury, Amor; Svečko, Rajko
Abstract: This paper presents multi-objective optimization-based robust controller design of a DC–DC boost converter, controlled with FPGA (Field Programmable Gate Array). The main aim of the proposed design technique is to obtain a fixed and low-order robust controller which is reliable and easy to implement on a low-cost real-time digital system. The improved proposed control design method with direct closed-loop pole position assessment using metric L 2, is based on robust optimal regional closed-loop pole assignment technique. The optimal solution has been obtained using multi-objective Pareto front search genetic algorithm. This paper also presents simulated and practical experimental results with implemented optimized robust controller on FPGA, controlling the DC–DC boost converter. For the sake of comparison with the proposed controller design method, an additional auto-tuned PID controller has been designed along with robust controllers based on mixed sensitivity loop-shaping method. Highlights: FPGA control of a DC–DC boost converter using a low-cost FPGA device. Robust fixed low-order controller structure design for a low-cost devices. A design based on a multi-objective genetic algorithm and Pareto front solutions. Improved method compared to the loop-shaping robust controller design method. Resulting controllers are tested on a real system of a DC-DC converter with FPGA.